GERD and Barrett's esophagus as indications for revisional surgery after sleeve gastrectomy: experience of a bariatric center of excellence IFSO-EC and narrative review. Issue 5 (3rd September 2021) - Silecchia, Gianfranco; Iossa, Angelo
ABSTRACT: Introduction: Laparoscopic sleeve gastrectomy is the most commonly performed bariatric procedure worldwide; due to its extensive impact and analysis, multiple procedure-related early and late complications have been described. Gastroesophageal reflux and Barrett's esophagus are highly debated issues related to sleeve gastrectomy in long-term follow-up. This review aims to explore the association between sleeve gastrectomy and gastroesophageal reflux in terms of their occurrence, and to analyze the protective or affecting factors. Areas covered: Gastroesophageal reflux and Barrett's esophagus after laparoscopic sleeve gastrectomy. Expert opinion: Gastroesophageal reflux is the Achilles' heel of sleeve gastrectomy and is affected by multiple procedure-related functional or mechanical factors (intrathoracic migration, stenosis, lower esophageal sphincter incompetence). Its postoperative incidence is about 30% with significant variability among groups, especially in terms of preoperative workup (lack of routine upper gastro-intestinal endoscopy and symptom assessment). Strict patient selection and mandatory pre-operative endoscopy are the primary steps taken to prevent and reduce the incidence of post-operative severe gastroesophageal reflux. However, patients should also be informed of the possibility of the 'de novo gastroesophageal reflux disease' (incidence – 22–50%) and the need for surgical revision in selected cases (0.5–7%).